Sensory characterization of pinni - a milk cereal based sweet using Quantitative Descriptive Analysis and Principal Component Analysis - Singh, Ravinder; Prasad, Writhdhama; Khamrui, Kaushik (Indian Journal of Dairy Science, 2019)
Pinni is a popular traditional milk-cereal based sweet of northern states of India viz., Punjab, Haryana and Delhi. Samples collected from Market QDA revealed a significant (p<0.05) difference in sensorial, physico-chemical, textural attributes of pinni among the market samples. PCA identified key six components composed of shape, crumbliness, cooked flavour, colour, firmness, oxidized flavour, gumminess, chewiness, cohesiveness, surface appearance and surface coating and moisture absorption, which governed 78.66% of the variation in the sensory scores of pinni. Hence, these attributes may be given prime importance while developing the product technology for industrial scale production.